Legal Implications of Determining A Missing Person in Relation to His Rights and Obligations As A Subject of Civil Law - Imaniyar, Nadhira; Ramadhani, Dwi Aryanti (Journal of Law, Politic and Humanities, 2025)
This study of legal implications of determining a missing person in relation to his rights and obligations as a subject of civil law explores the legal consequences of declaring a person missing (afwezigheid) on their civil rights and obligations in Indonesia. The status of missing persons creates legal uncertainty for families and related parties, especially in guardianship, divorce, and asset management matters. Using a normative juridical approach with statutory and case analysis, the research examines relevant laws including the Civil Code, Population Administration Law, Islamic Law Compilation, and court rulings. The results reveal a dual regulatory system between general courts and religious courts, leading to differences in procedures and legal effects. The declaration of missing status significantly affects three civil law areas: first, it allows appointment of guardians for children left behind; second, it serves as grounds for divorce after a specific period; and third, it permits appointing administrators to manage and protect the missing person’s property. The study concludes that harmonizing regulations on missing persons’ status is essential to provide legal certainty and comprehensive protection for all parties involved. Such harmonization would resolve procedural inconsistencies and jurisdictional overlaps, ensuring clearer legal frameworks and better safeguarding of rights and obligations in cases involving missing persons